Analysis of Daily Test Items In Arabic For Muhammadiyah Elementary School Sidoarum Yogyakarta - Nasikhah, Malikhatun; Wahidah, Zulfa Amalia (Asalibuna, 2020)
This study aims to determine the quality of the daily test items in Arabic class III SD Muhammadiyah Sidoarum Yogyakarta, in terms of the different power of the questions and the difficulty level of the questions. This research is a quantitative research because the research data is in the form of numbers and uses statistical analysis in the excel application. This research data collection by means of observation and documentation. Data analysis using the excel application program AnBuSo (Questionnaire Analysis) version 5. The results of the study show that the process of composing Arabic questions is not good, because the teacher does not pay attention to the stages used in the preparation of the questions so that the difference between the questions and the difficulty level of the questions is not balanced, and the teacher does not make the syllabus.Then the daily test questions in Arabic for grade III SD Muhammadiyah Sidoarum Yogyakarta, have 25 multiple choice questions, 6 match questions, 6 dot term questions, and 6 circle questions that match the correct words according to the picture. for multiple choice questions number 5,6,11, and 12 the difference power coefficient of 0.000 shows that the difference power of the questions is not good because they cannot differentiate the students' ability in answering the questions.then question number 5 the difficulty level coefficient of 0.000 difficult category. Problem numbers 6, 11, and 12 difficulty level coefficients for 1,000 easy categories. It is better if questions number 5,6,11 and 12 are deleted because they have unbalanced power of question difference and difficulty level. and for the description of the difference in power and the level of difficulty it is good, because there are no coefficients of 0,000 and 1,000.